The Effect of Adding Different Amounts of Lachancea thermotolerans together with Saccharomyces cerevisiae on Simultaneous Fermentation in Emir Wine Production - Hasan Tangüler; Mehmet Yetisen; Ayse Geylan Sanyol; Ayse Ezgi Tuncel; Turkan Turkmaya; Vecihe Bal; Hüseyin Erten (Turkish Journal of Agriculture: Food Science and Technology)
Our current research aimed to investigate the impacts of the use of indigenous yeast Saccharomyces cerevisiae with different amounts of Lachancea thermotolerans yeasts in mixed culture on the general composition, aroma compounds, sensory analysis and yeast growth of cv. Emir wine. The utilization of L. thermotolerans in mixed cultures reduced the total acidity of wines from 5.40 to 5.19 g/L (as tartaric acid). The acidity of high acid grapes musts obtained from various viticulture areas can be relatively decreased in wine production. In addition, there may be a slight decrease in the amount of ethyl alcohol. On the other hand, increasing the inoculum level of L. thermotolerans led to an increase in the amount of higher alcohols. However, the concentration of esters declined with the higher inoculum levels. According to the sensory evaluation, the most preferred wine was the one obtained with co-inoculation of S. cerevisiae and L. thermotolerans strains at the level of 5×106 and 1×108 cells/mL, respectively. As a result, it can be said that the use of L. thermotolerans yeast in different inoculum levels has a positive effect on wine fermentation.